Implementation of CORE (Connecting, Organizing, Reflecting, Extending) Strategy on Students' Connection Ability in Elementary Mathematics Subjects - Adinda Rahmah Rangkuti (Yayasan Zia Salsabila, 2023)
The key to the success of educators right on target for students is determined through the implementation of learning strategies. In fact, the CORE Strategy (Connecting, Organizing, Reflecting, Extending) aims to train students' connection skills, think critically, and be active in learning. The purpose of writing this article is to describe the implementation of the CORE strategy for students' connection abilities in mathematics at the elementary/MI level. This study uses a descriptive qualitative research method that aims to describe an object, phenomenon, or problem with the facts being studied. Data collection techniques were carried out using observation techniques, interviews, and documentation studies. Based on the results of this study it was found that the implementation of the CORE strategy could improve students' connection skills in mathematics. The student is active, gives a positive response when participating in the learning process, and understands the subject matter that has been taught. Thus, it is stated that the implementation of the CORE learning strategy in mathematics is categorized as appropriate for SD/MI children, as well as the students' connection abilities developing well and providing feedback in the ongoing learning process.